Odpowiedzi

2010-02-26T22:12:03+01:00
A) -2-2a+3 = -2a +1
b) 2a-3b+3a-2b =5a-5b
c) 2y-6y+4x-2x=2x-4y
d) 2x+3-6x-10= -4x-7
e) -x+2x+(-6)+x-4= -x+2x-6+x-4= 2x-10
1 5 1
2010-02-26T22:12:32+01:00
Wyrazy podobne, czyli "x" z "x", liczba z liczbą, "y" z "y"
a) -2-2a+3=1-2a
b) 2a-3b+3a-2b=5a-5b=5(a-b)
c) 2y-6y+4x-2x=-4y+2x
d) 2x+3-6x-10=-4x-7
e) -x+2x+(-6)+x-4=2x-10
1 5 1
2010-02-26T22:12:55+01:00
A) -2a+1
b) 5a-5b
c) -4y+2x
d) -4x-7
e) 2x-10

Jestem już trochę zmęczona, ale mam nadzieję, że jest dobrze. ;>
1 5 1